Work Talenta DNA as A Catalyzer Employee Performance - Catur Priyadi; Emiliana Sri Pudjiarti; Joko Rizkie Widokarti; Syahrial Shaddiq (Universitas Dharma Wacana, 2025)
Based on the identification of the problems explained above, this research proposal will focus on two research problems that can be formulated, namely: How is the individual behavior model based on a dynamic attitude to always follow the work culture to improve performance and. Is the proposed new concept of Work DNA Talent (WDT) able to bridge the relationship between leadership transformation and employee performance The three basic theoretical approaches that have been described previously, namely Talent Management theory, DNA theory, and Work Culture theory, are the basis for developing a new concept called Work Talent DNA (WTD). statistical analysis using structural equation models (SEM) through Analysis Moment of Structural (AMOS) software. 24.00. probability sampling with the Proportionate Stratified Random Sampling method. The population is 270 Millennial Generation ASN. The research findings prove that this concept has a significant effect on improving Employee Performance. Thus, Work Talent DNA acts as a mediating variable that links Transformational Leadership with Employee Performance, thus providing a new contribution to the development of modern human resource management theory